GPR88 promotes neurite outgrowth of sensory neurons via activation of Gi/o - Ün, Didem; Gilbert, Catherine; Steinkellner, Thomas; Salzer, Isabella; Freissmuth, Michael (Frontiers in Pharmacology, 2026)
IntroductionThe peripheral nervous system retains the intrinsic ability to regenerate: after nerve injury, axons can sprout and reinnervate their target organ. We hypothesized that this regenerative response was driven by a transcriptional program involving druggable gene targets that promote neurite outgrowth.MethodsSensory neurons were isolated from rat dorsal root ganglia (DRG) and cultured in vitro. Transcript levels were determined by sequencing of RNA. RNAscope was used to visualize GPR88 transcripts in individual subtypes of DRG neurons. Neurite outgrowth was quantified in the absence and presence of allosteric activators of GPR88 to generate concentration-response curves. Neuronal cultures were incubated in the presence of pertussis toxin and gallein to block Gi/Go- and βγ-dependent signalling, respectively.Results & DiscussionPlacing DRG neurons in culture severs their bipolar axons but they regrow spontaneously over several days. RNA sequencing revealed time-dependent differences in gene expression. The orphan G protein-coupled receptor GPR88 was robustly upregulated during the early phase of regeneration. A search in publicly available datasets confirmed that the mRNA encoding GPR88 was upregulated after peripheral nerve injury. RNAScope in situ hybridization visualized the expression of GPR88 in all major subtypes of DRG neurons. The allosteric activators of GPR88 (RTI-13951-33, racemic 2-PCCA and its enantiomers) promoted the neurite outgrowth in a concentration-dependent manner with EC50 values in the nanomolar range. Their effect was abolished by incubation with pertussis toxin and gallein. These observations identify GPR88 as a regulator of neurite outgrowth in DRG neurons and implicate Gi/Go as a component of the signaling pathway. The findings support the conclusion that GPR88 is a potential therapeutic target for accelerating peripheral nerve repair.